Peran Komunikasi Digital terhadap Kepuasan Pelanggan di Era Media Sosial - Widia Widia; Aprikia Dwi Khairunisyam; Piksi Ayuni; Yasrul Aditia (PT. Intelek Cendikiawan Nusantara, 2026)
This study aims to analyze the role of digital communication in influencing customer satisfaction in the era of social media, using a case study of Kerupuk A3 Palembang store on the Shopee e-commerce platform. This research employs a qualitative approach with a descriptive method using content analysis techniques. The data were collected from customer reviews, digital communication activities, and documentation in the form of screenshots related to interactions between sellers and customers. The analysis process includes data reduction, categorization, data presentation, and conclusion drawing. The results indicate that digital communication plays a significant role in shaping customer satisfaction. Key factors influencing customer satisfaction include the responsiveness of the admin, friendly communication style, flexibility in handling customer requests, and clarity of product information. Effective communication not only enhances customer satisfaction but also builds trust and encourages customer loyalty through repeat purchases and recommendations. Therefore, digital communication becomes a strategic factor for businesses in improving service quality and maintaining long-term relationships with customers in the social media era.